Pengaruh Dimensi Service Quality, Informasi Dan Image Pada Behavioral Intentions Yang Dimediasi Oleh Kepuasan Emosional - Herlina Rahmawati (Riset Manajemen dan Akuntansi, 2015)
High satisfaction tends to cause consumers to behave in a positive, emotional attachment to the brand or institution, and so a rational preference it can result high loyalty of consumer. For a service company one of the tools to support the competitive strategy for the better is to have a good quality of service. This study aimed to analyze the effect of service quality, information and images on the emotional satisfaction and behavioral intention The population in this study was the visitors Karanganyar Library and Archives. Sampling technique in this study using a non probability sampling and number of samples used by 50 respondents. Methods for collecting data using questionnaires, while the method of data analysis using path analysis. The results of this study demonstrate that reliability has positive and significant effect on emotional satisfaction. Responsiveness has positive effect but not significant on emotional satisfaction. Assurance no significant effect on emotional satisfaction. Access has positive and significant effect on emotional satisfaction. Communication no significant effect on emotional satisfaction. Empathy has positive and significant effect on emotional satisfaction. Information no significant effect on emotional satisfaction. Image no significant effect on emotional satisfaction. Reliability is not a significant effect on behavioral intentions. Responsiveness has positive and significant effect on behavioral intentions. Assurance has no significant effect on behavioral intentions. Empathy has positive and significant effect on behavioral intentions. Image has no significant effect on behavioral intentions. Emotional satisfaction has positive and significant effect on behavioral intentions. Keywords: quality of service, information, images, emotional satisfaction, behavioral intention